A retrospective study of the role of hypercapnia in patients with acromegaly - Junwei Guo; Wenhao Cao; Jinmei Luo; Rong Huang; Yi Xiao (BMC Pulmonary Medicine, 2023)
Abstract Background Acromegaly is a multisystemic disease characterized by an excessive release of growth hormone (GH) and insulin-like growth factor-1. Obstructive sleep apnea (OSA) is a common consequence of acromegaly, and hypercapnia is frequently observed in patients with acromegaly, OSA, and obesity. However, the effects of hypercapnia on acromegaly remain unknown. This study was designed to investigate whether there are differences in clinical symptoms, sleep variables, and biochemical remission after surgery for acromegaly in patients with OSA with or without hypercapnia. Methods A retrospective analysis was conducted involving patients with acromegaly and OSA. The pharmacotherapy history for acromegaly before surgery, anthropometric measures, blood gas, sleep monitoring data, and biochemical assays of hypercapnic and eucapnic individuals were collected 1–2 weeks before surgery. Univariate and multivariate logistic regression analyses were performed to determine the risk factors for failed postoperative biochemical remission. Results In this study, 94 patients with OSA and acromegaly were included. Among them, 25 (26.6%) had hypercapnia. The hypercapnic group had higher body mass index (92% vs. 62.3%; p = 0.005) and poorer nocturnal hypoxemia index. No serological differences were found between the two groups. According to the post-surgery GH level, 52 patients (55.3%) reached biochemical remission. Univariate logistic regression analysis revealed that diabetes mellitus (odds ratio [OR], 2.59; 95% confidence interval [CI], 1.02–6.55), instead of hypercapnia (OR, 0.61; 95% CI, 0.24–1.58), was associated with lower remission rates. Patients who received pharmacotherapy for acromegaly before surgery (OR, 0.21; 95% CI, 0.06–0.79) and had higher thyroid-stimulating hormone levels (OR, 0.53; 95% CI, 0.32–0.88) were more likely to have biochemical remission after surgery. Multivariate analysis further showed that only diabetes mellitus (OR, 3.29; 95% CI, 1.15–9.46) and preoperative pharmacotherapy (OR, 0.21; 95% CI, 0.06–0.83) remained significant. Hypercapnia, hormone levels, and sleep indicators had no effect on biochemical remission after surgery. Conclusions Single-center evidence shows that hypercapnia alone may not be a risk factor for lower biochemical remission rates. Correcting hypercapnia does not appear to be required before surgery. More evidence is needed to further support this conclusion.